Teacher and Student Approaches to Diagnosing Review Practices on Writing Skill - Rahime Şentürk; Gıyasettin Aytaş (Mehmet KURUDAYIOĞLU, 2022)
Writing, besides being one of the most important means of telling, is the process of expressing feelings and thoughts in a planned way. In this process, the arrangement that constitutes the lower step of the planning phase; the steps of reformatting the text, classifying the thoughts, adding new thoughts and redesigning are carried out. In this study, it was aimed to determine the use cases of the students' requirements for reviewing the texts in the teaching process, and then to increase the awareness levels of the teachers about the practices they do in the text editing phase. The field research method was used in the research and the data were collected with the 'Review Applications Diagnosis Form'. Descriptive statistics were used in the analysis of the data and the data were evaluated in the IBM SPSS Statistics 22 statistical program. For this purpose, 120 teachers who graduated from Turkish language teaching undergraduate program and 110 Turkish language teachers who graduated from Turkish language literature undergraduate program were reached. In the study, it was concluded that the students applied the strategies related to the revision and re-adjustment phase of the writing process in a limited and superficial manner. In addition, it was concluded that the students preferred the way of changing words, adding or removing words more in the process of reviewing the text. On the other hand, it was concluded that while the students frequently applied word replacement in their practice of reviewing their texts regarding the editing phase of the writing process, they applied the addition and removing less frequently in phrases, sentences and thoughts, however, they almost never applied replacement and reordering. While there was a statistically significant difference between Turkish and Turkish language literature teachers in terms of awareness of revision and correction procedures, there was no statistically significant difference in terms of evaluation status.